2022
DOI: 10.1111/iju.14804
|View full text |Cite
|
Sign up to set email alerts
|

Is transvaginal mesh procedure a potential measure for pelvic organ prolapse repair when performed by expert surgeons?

Abstract: The aim of this study was to verify the safety and efficacy of transvaginal mesh by analyzing the 2-year follow-up data of patients performed by a surgeon with a high volume of procedures. Methods: A total of 617 patients with pelvic organ prolapse underwent transvaginal mesh by a single surgeon. Complications and anatomical status of each patient were examined up to 24 months after surgery. Risk factors for the recurrence were also analyzed.Results: Regarding complications, we experienced 10 patients (3.8%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…14 There was also a report by a surgeon almost identical to the present study, which showed an anatomical recurrence rate of 2% at 2 years postoperatively. 6 In this study, we used the transobturator two-arm mesh, which produced therapeutic effects equivalent to those previously reported with the transobturator four-arm mesh. Therefore, the anterior mesh arms may be omitted in Japanese-style TVM surgery.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…14 There was also a report by a surgeon almost identical to the present study, which showed an anatomical recurrence rate of 2% at 2 years postoperatively. 6 In this study, we used the transobturator two-arm mesh, which produced therapeutic effects equivalent to those previously reported with the transobturator four-arm mesh. Therefore, the anterior mesh arms may be omitted in Japanese-style TVM surgery.…”
Section: Discussionmentioning
confidence: 77%
“…Takeyama et al reported that in young patients with advanced cystocele and uterine prolapse who underwent TVM surgery with a transobturator four-arm mesh similar to the Prolift type, the rate of recurrence was significantly higher than in older patients. 6 Padoa et al reported that in 52.2% of patients who underwent robot-assisted sacrocolpopexy for advanced cystocele, prolapse recurred. 30 TVM-A2 may be suitable for such cases, but the results may be the same even with a different technique.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations